Conversion of Branched-Chain Amino Acids to Corresponding Isoacids - An in vitro Tool for Estimating Ruminal Protein Degradability - Apajalahti, Juha; Vienola, Kirsi; Raatikainen, Kari; Holder, Vaughn; Moran, Colm A. (Frontiers in Veterinary Science, 2019)
In this paper we describe a study that evaluates the applicability of an in vitro fermentation model to assess the resistance of protein supplements to rumen degradation. The protein sources used were: soybean meal (SBM); whey protein (WHEY), which was expected to be rapidly degraded, and yeast-derived microbial protein (YMP), which was proposed to be resistant to rumen degradation. The basal diet was composed of grass silage and a commercial compound feed. The protein supplements were added at three isonitrogenous doses. Fermentation was monitored for 24 h and gas production, volatile fatty acids, lactic acid, and ammonia were analyzed at three timepoints. Protein degradation was estimated by determining the extent to which branched-chain amino acids (BCAA) introduced with the protein supplement were converted to corresponding branched-chain volatile fatty acids (BCVFA). At the highest dose of WHEY, 60% of introduced valine, leucine, and isoleucine was recovered as isobutyric, 2-methylbutyric, and isovaleric acid (products of BCAA decarboxylation and deamination), respectively. The BCVFA detected represented 50% of added BCAA with SBM, but <15% with YMP. Further indications that YMP protein is resistant to degradation were provided by analysis of ammonia. With YMP, the residual ammonia concentration only marginally exceeded that of the cultures with no protein supplementation, while it increased dose-dependently when the vessels were supplemented with WHEY or SBM. This suggests that with WHEY and SBM, the rate of deamination exceeded the rate of ammonia assimilation by bacteria. Residual ammonia and BCVFA, the two indicators of protein fermentation, were strongly correlated. Overall bacterial activity was monitored as yield of gas, volatile fatty acids, and bacteria. These three correlating parameters showed that WHEY only modestly stimulated fermentation, whereas SBM and YMP stimulated fermentation extensively, possibly owing to their higher carbohydrate content. The results presented suggest that the in vitro fermentation method was suitable for detecting differences in resistance of protein supplements to rumen degradation and following a full method validation could be a useful tool for diet formulation. The data obtained suggested that YMP was the most resistant and WHEY the most susceptible to degradation.